Comparative Analysis of Welfare State In The USA And India: Contexts, Approaches, And Outcomes - Nawaz, Saqib; Rasool, Tabasum; Bhat, Shabir (International Journal of Psychosocial Rehabilitation, 2019)
This paper examines the differing models of welfare states in the United States and India, highlighting the unique historical, cultural, and socio-economic contexts that shape their approaches to social welfare. It provides a comparative analysis of welfare states and capitalist states, focusing on their governance, economic management, social welfare provisions, equality, and political structures. By comparing the evolution, implementation, and outcomes of welfare policies in the USA and India, the study provides insights into how each nation addresses social inequalities and promotes economic stability. The analysis includes the role of government intervention, the blend of private and public sector involvement, the challenges of efficiency and outcomes, and the specific policies aimed at social equity. The paper underscores the importance of context-specific approaches to social welfare and offers valuable lessons for policymakers and scholars seeking to improve social welfare systems globally.